2015
DOI: 10.2112/jcoastres-d-13-00115.1
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial and Seasonal Pattern of Water Quality in the Sundarbans River Systems of Bangladesh

Abstract: Rahaman, S.M.B.; Rahaman, M.S.; Ghosh, A.K.; Gain, D.; Biswas, S.K.; Sarder, L.; Islam, S.S., and Sayeed, A.B., 2015. A spatial and seasonal pattern of water quality in the Sundarbans river systems of Bangladesh. Journal of Coastal Research, 31(2), 390-397. Coconut Creek (Florida), ISSN 0749-0208.Comprehensive field measurements were made in three major river systems (RSs) of the Sundarbans during October 2010 to August 2011 under post-monsoon, dry winter, and monsoon seasons to assess the pollution status. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The average soil salinity has already increased by 60% since 1980 (Aziz & Paul, ). Opportunistic harvesting of trees and heavy siltation in the internal channels are ongoing (Rahaman et al, ). Therefore, our findings lead us to conclude that additional harvesting, siltation, cuts in freshwater supply and range expansions of the generalists under projected sea level rise (Karim & Mimura, ) may convert the whole Sundarbans into a species‐poor homogeneous ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The average soil salinity has already increased by 60% since 1980 (Aziz & Paul, ). Opportunistic harvesting of trees and heavy siltation in the internal channels are ongoing (Rahaman et al, ). Therefore, our findings lead us to conclude that additional harvesting, siltation, cuts in freshwater supply and range expansions of the generalists under projected sea level rise (Karim & Mimura, ) may convert the whole Sundarbans into a species‐poor homogeneous ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The coastal belt of the country is facing enormous challenges in meeting freshwater demand due to limited water supply from the groundwater and surface water sources as they are affected by the various degrees of salinity and other water quality problems (Chowdhury et al 2014). Reports showed that about 53% of the coastal watersheds of Bangladesh are affected by various degrees of salinity (Minar et al 2013;Rahman et al 2015). The problem becomes intensified due to some climate change-associated hazards like sea-level rise, riverbank erosion, land accretion, insufficient and irregular rainfall, cyclones, tidal surges, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the irrigated waters can affect plant growth through toxicity, nutrient deficiency, or altering plant availability of nutrients (Ayers & Westcot 1985). A few studies have revealed that Kalapara is one of the vulnerable mid-coastal watersheds of Bangladesh with high to moderate degrees of salinity (Rahman et al 2015). These studies mainly focused on seasonal variations of salinity, the impact of salinity on agriculture, fisheries, land uses, crop production, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Sirajul Islam, Yousuf Ali, M. Humayun Kabir, Rofi M. Zubaer, Nowara Tamanna Meghla, Mausumi Rehnuma, Mir M. Mozammal Hoque (Islam et al, 2017;Islam et al, 2019). Thus, the nutrient concentration must be within suitable limit for a good aquatic environment and for better production of aquatic organisms (Rahaman et al, 2015). In the past decades, limnologists have developed many methods to assess the trophic status, including the character method (Rao, 1956), parameter method, the biotic indices method (Alba-Tercedor, 1996), the phosphorus budget model method (Dillon and Rigler, 1974) and the trophic state index method (Carlson, 1977).…”
Section: Introductionmentioning
confidence: 99%